Monitoring of self-healing in concrete with micro-capsules using a combination of air-coupled surface wave and computer-vision techniques. (July 2022) - Ahn, Eunjong; Kim, Hyunjun; Gwon, Seongwoo; Oh, Sung-Rok; Kim, Cheol-Gyu; Sim, Sung-Han; Shin, Myoungsu
This study mainly aims to investigate the applicability of the combination of air-coupled surface-wave and computer-vision techniques to the evaluation of self-healing in in situ concrete members. Small-scale beam specimens were made from ordinary concrete and concretes with solid- and liquid-type capsules; the capsules were employed as self-healing agents. To monitor the crack healing progress, surface-wave tests using an air-coupled transducer and contact receivers were conducted on each specimen in uncracked, cracked, and healed conditions after 7, 14, 28, and 63 days of water immersion. Additionally, a computer-vision technique involving image binarization and registration was applied to measure high-resolution crack information. The specimens containing the micro-capsules showed superior healing performance compared to the ordinary concrete specimens. After 63 days of self-healing, the spectral energy transmission ratio increased up to about 80% of the uncracked, while the crack area decreased up to about 94% of the fully cracked. The healing rate was estimated using the change in spectral energy transmission ratio strongly correlated with that estimated using the change in crack area.